Immune profiling of uveal melanoma identifies a potential signature associated with response to immunotherapy. Issue 2 (17th November 2020) - Qin, Yong; Bollin, Kathryn; de Macedo, Mariana Petaccia; Carapeto, Fernando; Kim, Kevin B; Roszik, Jason; Wani, Khalida M; Reuben, Alexandre; Reddy, Sujan T; Williams, Michelle D; Tetzlaff, Michael T; Wang, Wei-Lien; et al.
Abstract : Background: To date, no systemic therapy, including immunotherapy, exists to improve clinical outcomes in metastatic uveal melanoma (UM) patients. To understand the role of immune infiltrates in the genesis, metastasis, and response to treatment for UM, we systematically characterized immune profiles of UM primary and metastatic tumors, as well as samples from UM patients treated with immunotherapies. Methods: Relevant immune markers (CD3, CD8, FoxP3, CD68, PD-1, and PD-L1) were analyzed by immunohistochemistry on 27 primary and 31 metastatic tumors from 47 patients with UM. Immune gene expression profiling was conducted by NanoString analysis on pre-treatment and post-treatment tumors from patients (n=6) receiving immune checkpoint blockade or 4-1BB and OX40 dual costimulation. The immune signature of UM tumors responding to immunotherapy was further characterized by Ingenuity Pathways Analysis and validated in The Cancer Genome Atlas data set. Results: Both primary and metastatic UM tumors showed detectable infiltrating lymphocytes. Compared with primary tumors, treatment-naïve metastatic UM showed significantly higher levels of CD3+, CD8+, FoxP3+ T cells, and CD68+ macrophages. Notably, levels of PD-1+ infiltrates and PD-L1+ tumor cells were low to absent in primary and metastatic UM tumors. No metastatic organ-specific differences were seen in immune infiltrates. Our NanoString analysis revealed significant differences in a set of immune markers between responders and non-responders. A group of genes relevant to the interferon-γ signature was differentially up-expressed in the pre-treatment tumors of responders. Among these genes, suppressor of cytokine signaling 1 was identified as a marker potentially contributing to the response to immunotherapy. A panel of genes that encoded pro-inflammatory cytokines and molecules were expressed significantly higher in pre-treatment tumors of non-responders compared with responders. Conclusion: Our study provides critical insight into immune profiles of UM primary and metastatic tumors, which suggests a baseline tumor immune signature predictive of response and resistance to immunotherapy in UM.